Disparitas Antar Kecamatan Dan Strategi Pembangunan Ekonomi di Kabupaten Banyuwangi - Nur Anim Jauhariyah; Abdul Kholiq Syafa’at; Nurul Inayah; Lely Ana Ferawati Ekaningsih (Conference In Business, Accounting, And Management (CBAM), 2012)
The study was conducted 1) to Knowing the potential of each sector in Banyuwangi and 24 districts, 2) to analyze the economic disparity among districts in Banyuwangi. Analysis of the data used typology Klasen, Location Quotient (LQ), Analysis of Inter- District Disparities, Policy Analysis with Analytical Hierarchy Process (AHP). The results of the analysis of the economic development strategy in Banyuwangi is as follows: Klassen Quotients result shows that the sector can be categorized as an advanced and fast-growing sector (primary sector) refers Agriculture and the sector is underdeveloped sectors of Manufacturing, Trade, Hotels and Restaurants, Transport and Communications, and Services. The results of the analysis of the seed sector LQ sectors have LQ values> 1 consists of Agriculture, mining and quarrying sector, and financial sector, leasing, and corporate services. The agricultural sector is a sector that is still contributing to economic growth in Banyuwangi. AHP analysis results to find policy solutions from primary data analysis indicates that the sector is still very optimistic about the potential and developed in accordance with the year Banyuwangi analysis is still optimistic on the agricultural sector, followed by hospitality sector saw the potential of tourism in Banyuwangi is still beautiful and clean, potential to be optimized to increase revenue Banyuwangi. The results of the analysis of disparities among districts using Williamson Index and Theil Entropy Index that Wongsorejo District, Muncar, Kalipur, and Licin possessed a relative index of inequality is higher than the other sub-districts.Keywords: disparities, policy strategies, the potential of the distric.